Health Literacy and Self-Efficacy among University Students in the United States - Beasley, Lauren; Hoffman , Steven; McCracy , Emily; Wallace, Tucker (Social Welfare: Interdisciplinary Approach, 2025)
Research suggests that college can be a time of high stress, serious mental health challenges, and high-risk substance use habits. Self-efficacy (one’s belief in their abilities) and health literacy (one’s ability to read, understand, and apply health information) are two factors that promote wellbeing and positive health behaviors among college students, but little research has been conducted so far that looks at the relationship between these protective factors. Thus, this study examined the connection between self-efficacy and health literacy among American college students. Data were collected by using quota sampling from 410 undergraduate students. Health literacy was measured by using the All Aspects of Health Literacy Scale, whereas self-efficacy was measured by using the General Self-Efficacy Scale. Self-efficacy was positively predicted by functional (b = 2.77; d = 0.26; p < 0.001), communicative (b = 2.94; d = 0.27; p < 0.01), and critical health literacy (b = 1.51; d = 0.14; p < 0.05). Our findings suggest a positive relationship between self-efficacy and health literacy in the college student population in the United States. Colleges and universities can work to provide accessible health literacy resources and education, as this type of health literacy education may also lead to higher self-efficacy and increased overall wellbeing.
Keywords: college students; mental health; university programming